Influência do tipo de sistema de polimento na rugosidade superficial de uma resina tipo bulk fill - Santana, Carlisson Rodrigues de (2019)
In view of the diversity of existing composite resins, it is of paramount importance to study these to verify the employability in the clinical scope, so the objective of this work is to evaluate the efficiency of the polishing systems in test specimens of traditional and Bulk Fill resins. The study was performed after selection of two types of resins being a nano-hybrid (Charisma® Diamond Heraeus Kulzer) and a Bulk Fill (FGM) with 1 mm thick specimens. Polishing techniques Sof-Lex abrasive discs (3M ESPE), and Jiffy Polisher abrasive impregnated silicone discs (Ultradent) were used as polishing techniques, the resins were grouped according to their respective polishing group and polished judiciously. After the polishing phase, the surface roughness of each specimen was measured using a Mitutoyo SJ-410 model rugosimeter, which provides in micrometers (µm). The analysis of the data occurred through two statistical approaches. Initially, in the descriptive statistics, the data of dispersion and central tendency were presented. In the analytical statistic, the two-way ANOVA test was performed (p ? 0.05) and in cases where statistically significant differences were found, Tukey's post-hoc test was applied to verify at what levels these differences would be present. It can be concluded that bulk fill resins have been influenced more by polishing systems, especially after the use of abrasive-impregnated silicon disks, which left it with greater surface roughness.